2013
DOI: 10.1371/journal.pone.0075081
|View full text |Cite
|
Sign up to set email alerts
|

How to Decrease Suicide Rates in Both Genders? An Effectiveness Study of a Community-Based Intervention (EAAD)

Abstract: BackgroundThe suicide rate in Hungary is high in international comparison. The two-year community-based four-level intervention programme of the European Alliance Against Depression (EAAD) is designed to improve the care of depression and to prevent suicidal behaviour. Our aim was to evaluate the effectiveness of a regional community-based four-level suicide prevention programme on suicide rates.MethodThe EAAD programme was implemented in Szolnok (population 76,311), a town in a region of Hungary with an excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 22 publications
3
58
2
4
Order By: Relevance
“…107109 In particular, supporting physicians via an informational website, increasing liaison between physicians and psychiatric facilities, conducting public education campaigns to train key community facilitators in the recognition of depression and suicide risk, and providing a suicide hotline may all be important aspects of prevention strategies. 110 Collaborative care, in which care management for psychiatric disorders is co-located on site in primary care, has been shown to provide significant benefits over usual care in outcomes for depression and anxiety, 111 and to improve SI in depressed, older patients. 112 …”
Section: Interventions To Prevent or Treat Sbmentioning
confidence: 99%
“…107109 In particular, supporting physicians via an informational website, increasing liaison between physicians and psychiatric facilities, conducting public education campaigns to train key community facilitators in the recognition of depression and suicide risk, and providing a suicide hotline may all be important aspects of prevention strategies. 110 Collaborative care, in which care management for psychiatric disorders is co-located on site in primary care, has been shown to provide significant benefits over usual care in outcomes for depression and anxiety, 111 and to improve SI in depressed, older patients. 112 …”
Section: Interventions To Prevent or Treat Sbmentioning
confidence: 99%
“…Interventions were predominantly complex/multimodal (i.e. characterized by several different modes of activity or occurrence), encompassing awareness campaigns (Hübner-Liebermann et al, 2010;Matsubayashi et al, 2014;Ono et al, 2013;Szekely et al, 2013;Wang et al, 2013); training of community 'gatekeepers' (Hübner-Liebermann et al, 2010;Knox et al, 2003;Ono et al, 2013;Shelef et al, 2016); psychological support (Britton et al, 2014;Chen et al, 2012 ; 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Knox et al, 2003;Mishara et al, 2005;Nakao et al, 2007;Ono et al, 2013;Pratt et al, 2015;Saewyc et al, 2014); and educational initiatives targeted to either GPs or depressed or suicidal men (Hübner-Liebermann et al, 2010;Knox et al, 2003;Nakao et al, 2007;Shelef et al, 2016;Szanto et al, 2007;...…”
Section: Male Suicide Prevention Interventionsmentioning
confidence: 99%
“…Male suicide is a significant health concern requiring urgent attention, and the growing evidence of male-specific risk factors has important implications for planning and evaluating suicide prevention interventions. Several countries have attempted to implement suicide prevention programmes (Althaus & Hegerl, 2003;Szekely et al, 2013), which typically involve multisectoral strategies that aim to address the range of causes at an individual and population level, with particular attention to mental health and improved screening of depressed patients in primary care. Previous reviews of reported on important gender differences in suicide risk and behaviour (Mann et al, 2005;Zalsman et al, 2016).…”
mentioning
confidence: 99%
“…This study aims to answer:Does the implementation strategy of SUPRANET lead to the expected EAAD outcomes [6,7,8,9] in terms of: Reduced suicidal ideation and behaviour and psychological distress?Reduced stigma and taboo and improved attitude towards seeking help?Increased help seeking behaviour to the helpline of 113 Suicide Prevention? …”
Section: Evaluation Of the Feasibility And Impact Of Supranetmentioning
confidence: 99%